The structure of language : an introduction to grammatical analysis - Pavey, Emma L. (Cambridge, UK. : Cambridge University Press, 2010)
'Most of the time we communicate using language without considering the complex activity we are undertaking, forming words and sentences in a split second. This book introduces the analysis of language structure, combining both description and theory within a single, practical text. It begins by examining words and parts of words, and then looks at how words work together to form sentences that communicate meaning. Sentence patterns across languages are also studied, looking at the similarities and the differences we find in how languages communicate meaning. The book also discusses how context can affect how we structure our sentences: the context of a particular language and its structures, the context of old and new information for us and our addressee(s), and the context of our culture'--
Includes bibliographical references (p. 383-397) and index.
Keywords: Grammar, Comparative and general; Semantics